P3.226 Pre-Exposure Prophylaxis (PrEP) is Estimated to Be a Cost-Effective Addition to Antiretroviral Therapy (ART) For HIV Prevention in a Generalised Epidemic Setting. (13th July 2013) - Ying, R; Celum, C; Baeten, J; Murnane, P; Hong, T; Krows, M; Rooyen, H van; Humphries, H; Hughes, J P; Barnabas, R
Abstract : Background: In KwaZulu-Natal, South Africa, young women face an extraordinarily high risk for HIV acquisition, with annual incidence estimates of 6%. ART-based strategies for HIV prevention have the potential to significantly decrease HIV incidence, but the impact of PrEP in addition to ART scale-up is undefined. Modeling studies suggest that PrEP targeted to highest-risk groups could maximise benefits and contain costs. Methods: We developed a deterministic transmission model of HIV that stratifies the population by age, sexual activity, and includes HIV infection stage. The model was parameterized using data from community-based HIV counselling and testing studies in KwaZulu-Natal and validated using independent HIV prevalence and incidence estimates. We estimated the effectiveness and cost-effectiveness of a 'test and treat' scenario, targeted PrEP by age and sexual activity, and general PrEP provision. Each scenario was in addition to anticipated baseline ART scale-up for CD4≤ 350 from 35% in 2013, as observed in KwaZulu-Natal, to 60% in 2018 (following national guidelines). We assumed PrEP efficacy of 70%. Results: 'Test and treat' (ART for 80% of all HIV-positive persons) reduced HIV incidence by 58% and averted 25% of cumulative infections by 2025, at an additional 39, 900 per infection averted compared to baseline ART scale-up. PrEP targeted to 60% of 20–29-year-olds, in addition to baseline ART scale-up, reduced incidence by 42% and averted 22% of infections at an additional 22, 500 per infection averted, whereas PrEP targeted to 80% of high-risk individuals reduced incidence by 33% and averted 13% of infections at an additional 7, 400 per infection averted. PrEP coverage of 20% of the general population reduced incidence by 37% and incident infections by 18%, at an additional 26, 900 per infection averted. Conclusion: In a generalised HIV epidemic setting PrEP is a cost-effective addition to ART, with targeted PrEP being more cost-effective than generalised PrEP distribution.